2012
DOI: 10.1055/s-0032-1327221
|View full text |Cite
|
Sign up to set email alerts
|

Kommunikation im Team und Burnout

Abstract: Zusammenfassung Fragestellung: Kommunikation ?ber Therapiebeschr?nkung ist ein wesentliches Element der Zusammenarbeit im interdisziplin?ren Team auf Intensiv- und Palliativstationen. Ziel der Untersuchung war, Aspekte der Kommunikation im Kontext von Therapiebeschr?nkungen (TB) und Burnout bei den Mitarbeitern beider Stationen zu vergleichen. Methode: Mitarbeiterbefragung auf Intensivstationen (ITS, 72 Betten) und Palliativstation (PS, 12 Betten). Der Fragebogen enthielt das Maslach Burnout Inventar (MBI) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Accordingly, two survey studies of hospice teams in the United States found no differences between the professions (e.g., nurses, physicians, social workers, and chaplains) in their ratings of the quality of interdisciplinary collaboration [ 13 , 15 ]. Except for small single-center studies, little is known about interprofessional/interdisciplinary collaboration in inpatient palliative care units (PCUs) [ 16 , 17 ]. We conducted a single-center study comparing experiences in the context of end-of-life decision-making experiences between ICU and PCU staff and found that PCU staff gave better ratings of the interaction within the team, and while ICU nurses rated interaction poorer than ICU physicians, ratings of PCU nurses and PCU physicians did not differ [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, two survey studies of hospice teams in the United States found no differences between the professions (e.g., nurses, physicians, social workers, and chaplains) in their ratings of the quality of interdisciplinary collaboration [ 13 , 15 ]. Except for small single-center studies, little is known about interprofessional/interdisciplinary collaboration in inpatient palliative care units (PCUs) [ 16 , 17 ]. We conducted a single-center study comparing experiences in the context of end-of-life decision-making experiences between ICU and PCU staff and found that PCU staff gave better ratings of the interaction within the team, and while ICU nurses rated interaction poorer than ICU physicians, ratings of PCU nurses and PCU physicians did not differ [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Except for small single-center studies, little is known about interprofessional/interdisciplinary collaboration in inpatient palliative care units (PCUs) [ 16 , 17 ]. We conducted a single-center study comparing experiences in the context of end-of-life decision-making experiences between ICU and PCU staff and found that PCU staff gave better ratings of the interaction within the team, and while ICU nurses rated interaction poorer than ICU physicians, ratings of PCU nurses and PCU physicians did not differ [ 16 ].…”
Section: Introductionmentioning
confidence: 99%